Peran Limbah Bahan Organik Pada Lubang Resapan Biopori Terhadap Sifat Kimia Tanah Di Lahan Pasca Tambang - Raziv Rahman; Emmy Sri Mahreda; Basir Basir; Bdaruddin Badaruddin (Universitas Lambung Mangkurat, 2020)
Biopore infiltration hole are hole made for run-off flow which if allowed to cause erosion and can remove the topsoil, causing soil fertility to be reduced. The use of biopori infiltration holes can be maximized by adding organic matters into the hope that in addition to absorbing water it can increase soil fertility. The liquid waste of tofu and meranti litter is an organic matters are used in this study, by adding organic matters to the biopori hole. This study aims to look at the effect of providing organic matters in the biopore hole derived from tofu and litter liquid waste on the value of pH, C-Organic, and post-mining CEC. This study was an experimental study in the field using a completely randomized design of one factor, namely organic matters with six levels, namely without organic matters and using 25 g, 50 g, 75 g, and 100 gr organic matters given to the biopori hole in incubation for one month later Soil samples taken were analyzed for pH, C-organic, and CEC. The results showed that the treatment only affected the soil's pH value. Organic material provided in the biopori hole is thought to have not completely decomposed, causing the soil around the biopori infiltration hole to remain acidic. The acidity of the soil is due to the gases produced during the decomposition process. Changes in soil pH ranged from 4.36 to 4.65 by administering 75g of organic matters from tofu liquid waste and meranti litter. This research is useful in post-mining land reclamation in increasing soil fertility, with the improvement of soil chemical properties such as pH will slowly improve the physical and biological properties of the soil so that it can be used as cultivation land.